In vitro antimicrobial activity of endodontic sealers, MTA-based cements and Portland cement. - Tanomaru-Filho, Mário; Tanomaru, Juliane Maria Guerreiro [UNESP]; Barros, Danilo B; Watanabe, Evandro; Ito, Izabel Y (Nihon University School of Dentistry, 2007)
The aim of this study was to evaluate the antimicrobial activity of different root-end filling materials - Sealer 26, Sealapex with zinc oxide, zinc oxide and eugenol, white and gray Portland cement, white and gray MTA-Angelus, and gray Pro Root MTA - against six different microorganism strains. The agar diffusion method was used. A base layer was made using Müller-Hinton agar (MH) and wells were formed by removing the agar. The materials were placed in the wells immediately after manipulation. The microorganisms used were: Micrococcus luteus (ATCC9341), Staphylococcus aureus (ATCC6538), Escherichia coli (ATCC10538), Pseudomonas aeruginosa (ATCC27853), Candida albicans (ATCC 10231), and Enterococcus faecalis (ATCC 10541). The plates were kept at room temperature for 2 h for prediffusion and then incubated at 37 degrees C for 24 h. Triphenyltetrazolium chloride 0.05% gel was added for optimization, and the zones of inhibition were measured. Data were subjected to the Kruskal-Wallis and Dunn tests at a 5% significance level. The results showed that all materials had antimicrobial activity against all the tested strains. Analysis of the efficacy of the materials against the microbial strains showed that Sealapex with zinc oxide, zinc oxide and eugenol and Sealer 26 created larger inhibition halos than the MTA-based and Portland cements (P < 0.05). On the basis of the methodology used, it may be concluded that all endodontic sealers, MTA-based and Portland cements evaluated in this study possess antimicrobial activity, particularly the endodontic sealers.
Keywords: root canal filling material; bacterium; Candida albicans; comparative study; drug effect; endodontics; Enterococcus faecalis; Escherichia coli; immunodiffusion; microbiological examination; Micrococcus luteus; Pseudomonas aeruginosa; Staphylococcus aureus; Bacteria; Immunodiffusion; Microbial Sensitivity Tests; Retrograde Obturation; Root Canal Filling Materials